Peeking at Peak Oil - Aleklett, Kjell; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
The term “Peak Oil” was born in January 2001 when Colin Campbell formed the Association for the Study of Peak Oil & Gas (ASPO). Now, Peak Oil is used thousands of times a  day by journalists, politicians, industry leaders, economists, scientists and countless others around the globe. Peak Oil is not the end of oil but it tells us the end is in sight. Anyone interested in food production, economic growth, climate change or global security needs to understand this new reality. In Peeking at Peak Oil Professor Kjell Aleklett, President of ASPO International and head of the world’s leading research group on Peak Oil, describes the decade-long journey of Peak Oil from extremist fringe theory to today’s accepted fact: Global oil production is entering terminal decline. He explains everything you need to know about Peak Oil and its world-changing consequences from an insider’s perspective. In simple steps, Kjell tells us how oil is formed, discovered and produced. He uses science to reveal the errors and deceit of national and international oil authorities, companies and governments  too terrified to admit the truth. He describes his personal involvement in the intrigues of the past decade. What happens when a handful of giant oil fields containing two thirds of our planet’s oil become depleted? Will major oil consumers such as the EU and US face rationing within a decade? Will oil producing nations conserve their own oil when they realize that no one can export oil to them in the future? Does Peak Oil mean Peak Economic Growth? If you want to know the real story about energy today and what the future has in store, then you need to be Peeking at Peak Oil. Exposes the facts and implications of the most  “inconvenient truth” in science Highlights the major social and economic impacts of the Peak of the Oil Age Provides an authoritative introduction in easy-to-understand language Features original illustrations by one of Sweden’s leading graphic artists, Olle Qvennerstedt.
Prologue -- 1. Introduction -- 2. Peak Oil -- 3. A world addicted to oil -- 4. The global oil and gas factory -- 5. How to find an oilfield -- 6. The oil industry’s vocabulary -- 7. The art of producing (extracting) oil -- 8. The size of the tap - the laws of physics and economics -- 9. The Elephants – the giant oilfields -- 10. Unconventional oil, NGL and the Mitigation Wedge -- 11. The peak of the Oil Age -- 12. Oil from Deep Water –the tail end of oil production -- 13. Peeking at Saudi Arabia - “Twilight in the desert” -- 14. Russia and the USA - the oil pioneers| -- 15. China and Peak Oil -- 16. Peak transportation -- 17. Peak Oil and climate change -- 18.  Why military and intelligence agencies are “Peeking at Peak Oil” -- 19. How can we live with Peak Oil? -- 20. An inconvenient Swede -- Epilogue -- Index.
Keywords: Environmental management; Energy policy; Energy and state; Fossil fuels; Environmental economics; Economic geology; Environmental Management; Energy Policy, Economics and Management; Fossil Fuels (incl. Carbon Capture).; Environmental Economics; Economic Geology